Holy foolery in the life of Japan a historical overview - Higuchi, Kazunori 1959- (LTCB international library selection, 2015)
"On the following pages, we will retrace the origins and evolution of holy foolery in Japan. We will witness its near extinguishment through the process of modernization and globalization. We will see why Japan needs holy foolery more than ever. And we will identify contemporary traces that suggest a basis for optimism about laughter's possible resurgence"--From jacket.